English plus : student's book. (Oxford : University Press, 2010)
English Plus is a four-level course for teenagers. It is a flexible and supportive course that builds confidence through graded practice. A supportive course that helps students of all abilities build confidence through graded practice. The flexible package makes it ideal for mixed-ability classes, and varying teaching loads. English Plus develops students' communication skills through a structured and methodical approach, helping students to achieve their individual learning outcomes in every lesson.
Keywords: Engels -- Secundair onderwijs